Mark: an introduction and study guide : shaping the life and legacy of Jesus - Smith, Abraham (T & T Clark study guides to the New Testament, 2017)
Introduction: Reshaping the memory of a teacher and his movement -- Mark as a life about Jesus -- Mark as a life for Jesus' followers -- Jesus as a prophetic envoy -- Jesus as a powerful broker -- Jesus as a philosophical hero